(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Nowadays, planetary health and climate change issues impact all areas of society. The alignment of physical activity promotion with planetary health has been a recurring topic at recent HEPA conferences, yet many organisations still hesitate to prioritise it on their agendas. To better understand the current landscape, opportunities, and barriers, the HEPA Working Group on Environmental Approaches to HEPA Promotion conducted a survey. Methods: The Working Group developed a questionnaire to explore the relevance of planetary health in the context of physical activity promotion. The survey included questions on participants’ professional sectors, the perceived importance of planetary health both personally and within their organisations (rated on a scale from 1 to 10), as well as open-ended questions about perceived barriers and opportunities for integrating planetary health into their organisational agendas. Results: Overall, 189 people participated in the survey. The majority of respondents consider planetary health highly important on a personal level, with 76% rating it 8 or higher out of 10. In contrast, when asked about the importance of planetary health for their organisation, only 43% rated it 8 or higher, while 29% felt the topic is not very important in their organisation, rating it 5 or lower. In respondents’ opinion, barriers to integrating planetary health in organisations are mainly due to political, financial, and institutional challenges, such as lack of political will, insufficient funding, competing priorities, and limited support or understanding at multiple levels. Cultural and behavioural obstacles also play a major role, including resistance to change, old habits, lack of awareness or training, and discomfort with shifting responsibilities or expectations. Conclusions: These findings highlight a clear gap between personal commitment to planetary health and perceived organisational prioritisation. Addressing this disconnect will require not only structural and policy-level changes, but also cultural shifts, increased awareness, and strategic efforts to embed sustainability across all levels of organisational practice. Support/Funding Source: No specific funding. Keywords: Planetary health, climate change, sustainability